2011
DOI: 10.1186/1743-422x-8-393
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine plus adefovir combination therapy versus entecavir monotherapy for lamivudine-resistant chronic hepatitis B: a systematic review and meta-analysis

Abstract: BackgroundChronic hepatitis B virus (HBV) infection represents a serious global health problem and resistance to lamivudine (LAM) has become a serious clinical challenge. Previous rescue therapy for the treatment of chronic LAM-resistant hepatitis B infected patients included switching to entecavir (ETV) and adding adefovir (ADV) or tenofovir (TFV). At present, switching to ETV is not recommended for rescue therapy for LAM-resistant chronic hepatitis B (CHB). The aim of this report was to determine whether add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 41 publications
2
32
1
Order By: Relevance
“…It is clear that ETV is the most potent antiviral agent when TDF is not available. Recently, Sheng et al (24) reported LAM plus ADV combination therapy was more effective and produced longer-lasting effects than switching to ETV monotherapy in treating CHB patients with LAM resistance. Similarly, Kim et al (25) found ADV add-on treatment in patients with LAM-resistant CHB suppressed HBV replication more effectively than ETV or ADV monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that ETV is the most potent antiviral agent when TDF is not available. Recently, Sheng et al (24) reported LAM plus ADV combination therapy was more effective and produced longer-lasting effects than switching to ETV monotherapy in treating CHB patients with LAM resistance. Similarly, Kim et al (25) found ADV add-on treatment in patients with LAM-resistant CHB suppressed HBV replication more effectively than ETV or ADV monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clearance of HBV DNA was seen in seven out of eight (78%) of the HBeAg negative children and five out of 22 (23%) of the HBeAg positive [112]. No safety data were presented in this pediatric study, however adverse effects of entecavir in adult studies have been minimal [105,106]. As with all the nucleos(t)ide analogues, lactic acidosis with severe hepatomegaly and steatosis has been reported [113].…”
Section: Treatmentmentioning
confidence: 99%
“…A recent meta-analysis has demonstrated that a combination therapy with lamivudine and adefovir dipivoxil is more effective and produces long-lasting effects than switching to entecavir monotherapy in treating chronic hepatitis B patients with lamivudine resistance. However, taking into account the practical benefits and the limitations of adefovir dipivoxil, individualized therapy will be needed in patients with a prior history of lamivudine-resistant infections [54] . Entecavir rescue therapy for 96 wk is less efficacious in patients with lamivudine/adefovir dipivoxil-refractory HBV, particularly in those who have an initial HBV DNA of > 10 7 copies/mL.…”
Section: Nasmentioning
confidence: 99%